Track level fusion algorithms for automotive safety applications - Duraisamy, B.; Schwarz, T.; Wohler, C. (2013 International Conference on Signal Processing Image Processing and Pattern Recognition (ICSIPR), 2013)
Fusion of information from different sensor systems is vital for automotive safety systems. In a typical automotive sensor fusion setup the fusion can be a measurement fusion or a track level fusion in a centralized fusion center. Track level fusion is desired due to communication, computation and organizational constraints. Track level fusion algorithms have to deal with different correlation issues among the sensor systems and the fusion center that maintains the global track. This correlation problem leads to a degraded fusion estimate which is not desirable in a safety and time critical application. This paper presents an overview of track level fusion algorithms to fuse two homogenous sensor systems and evaluates their performance.